Investigating binding positions for skis of similar mechanical characteristics - Edgecombe, T.; Stefanyshyn, D. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The dynamics of a turning ski are sensitive to the magnitude, direction, and location of the forces and moments applied by the skier, the mechanical characteristics of the ski, and the interaction between ski and snow. Binding position and, therefore, the location of applied skier forces, has an effect on the kinetics of the turning ski [1]. There is not, however, a consistent method of defining binding position among manufacturers, which could lead to irrelevant performance comparisons between skis. The current study quantifies the difference between binding positions for skis of similar geometry and stiffness.